Antioxidant, Cytotoxicity and Antitumor of Bergia suffruticosa (whole plant) - Elshiekh, Yasmin Hassan; Abdelmageed, Mona A.M. (International Journal of Scientific Research in Biological Sciences, 2019)
Bergia suffruticosa (Elatinaceae) is a plant that is collected from western Sudan. It is popularly used traditionally in the treatment as wounds healer and osteitis. This research aims to screen the cytotoxicity as well as antioxidants and the impact as antitumor of Bergia suffruticosa metabolites. Metabolites were extracted using different organic solvents to increasing polarity. The antioxidant was assessed using free radical scavenging activity DPPH. The petroleum ether extract was revealed the strongest antioxidant with IC50 89±0.01µg/ml, while the aqueous extract was revealed no antioxidant activity. The cytotoxicity was evaluated using the Brine shrimp lethality assay. Petroleum ether metabolites revealed high cytotoxicity with LD50 0.04ppm while the other metabolites were exhibited no cytotoxicity. The antitumor activity was assessed using SRB assay against tumor cell lines, breast carcinoma cell line (MCF7), Prostate carcinoma cell line (PC3), colon carcinoma cell line (HCT116). All metabolites were revealed activity against all cancer cells tested. The highest activity against breast cancer was exhibited by ethyl acetate with IC50 17 µg/ml. the petroleum ether extract was revealed the highest activity against prostate cancer cells with IC50 17.9 µg/ml.